Estudo químico dos organismos marinhos Aplysina fistularis Pallas e Sargassum polyceratium Montagne. - Lira, Narlize Silva (2012)
Algae and marine sponges have been the targets of important scientific researches in the last 50 years, with a large number of secondary metabolites isolated and identified, showing a wide structural variety where certain compounds are useful in characterizing classes of algae and sponges fact of great importance for chemists, taxonomists and ecologists. These substances exhibit many biological activities, such as defense against consumers and competitors, and colonial and pathogen organisms; or they display reproductive function. This thesis describes the results from the chemical study of Sargassum polyceratium Montagne, a seaweed from the Sargassaceae family, and Aplysina fistularis Pallas, a marine sponge from the Aplysinidae family. Both species had their chemical constituents identified by spectroscopic methods such as IR, mass and 1H and 13C-1D and -2D NMR, and by comparison with literature. The following porphirinic derivatives were isolated from S. polyceratium: 132-hydroxy-(132-R)-phaephytin a, 132-hydroxy-(132-S)-phaeophytin a,phaeophytin a and the steroid fucosterol. The chemical study of A. fistularis led us to the reisolation of the alkaloid and acetamide: 2-(3,5-dibromo 4methoxypheny,N,N,Ntrimethylethanamonium and (3,5-dibromo-4-ethoxy-1-hydroxy-4-methoxycyclohexa-2,5-dienyl) acetamide, and to the isolation of alkaloid 3,5-dibromo-4-[3 dimethylamonium]propoxyphenyl]-N,N,N trimethylethanamonium (aplysfistularine),reported for the first time. The ethanolic extract from S. polyceratium was evaluated for psicopharmacological effects, showing behavioral changes of CNS depressant type. The ethanolic, hexanic and dichloromethanic extracts as well as the mixture (132-hydroxy-(132-R)-phaephytin a and 132-hydroxy-(132-S)-phaeophytin a) were not capable of inhibiting the growth of the tested lineages, showing negative antimicrobial activity. However they were capable of modifying the antibiotic activity, modulating the bacterial resistance between 2x to 4x. The isolated compounds from A. fistularis show inhibition of the DNA enzyme Topoisomerase II-α, with further biological studies needed for determining the compounds potency. Therefore, the present results contribute for the chemical study of marine organisms from species S. polyceratium and A. fistularis.